Effect of silicon nitride on physical properties of SBR. (2021) - Harikrishnan, R.; Anirudh Mohan, T.P.; Rahulan, N.; Gopalan, Sundararaman
Abstract: In this research paper, the effect of silicon nitride (Si3 N4 ) on physical properties of Styrene Butadiene Rubber were studied. Tensile strength, cure time, tear strength and wear resistance were determined and compared for different compositions of silicon nitride on the rubber. The compositions of Si3 N4 were 2%, 4%, 6%, 8% and 10% by weight. Samples were prepared and tested successfully. Required properties were determined from the test observations. The tensile, tear and wear properties of the rubber found to be improved in the composite form for many compositions.